Multiband MIMO antenna for wireless devices - Hassan Khalaf, Sarah (2015)
A Design of compact Multiple-Input-Multiple-Output (MIMO) Microstrip Patch Antenna that has 4 ports, been designed and implemented. The proposed antenna consists of four ports with two patches operates at LTE frequencies and two Patches operates at WLAN frequency. The antenna is fabricated on an inexpensive FR4 a dielectric constant ofer=4.4, loss tangent of tan d=0.019, with thickness of substrate that is 1.6-mm and the thickness of patch is 0.035 mm. The measured results represents that the proposed antenna obtained a reasonable bandwidth for LTE and WIFI applications defined by 10-dB return loss. Furthermore, The S-Parameters of antenna are simulated and measured. In this project, design structure of the MIMO antenna four ports and substrate has been employed to broaden the bandwidth. Since MIMO antenna, high gain and directivity can be achieved. Simulation by using CST microwave studio program and measurement on the final prototype antenna were carried out and compared. A MIMO system characteristic evaluation of a four port MIMO antenna is performed. A four port antenna for wireless applications is designed, the antenna shows good pattern diversity low correlation coefficient.